2015
DOI: 10.1890/es14-00327.1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat configuration affects spatial pattern of β diversity of insect communities breeding in oyster mushrooms

Abstract: Abstract. Theory predicts that spatial structure can mediate interactions that affect species diversity in a patchy environment. A rarely considered effect of spatial structure on biodiversity is the interplay of spatial habitat arrangement with species interactions at multiple spatial scales. We investigated how spatial habitat arrangement and predation mediate the assembly of the larval communities of fungivorous insects breeding in the oyster mushroom, Pleurotus ostreatus (Jacq. ex Fr.) P.Kumm in a North Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Instead, most examinations of environmental difference and geographic distance have done so at a single scale (e.g., Fluck et al, 2020; Stehn & Roland, 2018) or compared regions (e.g., Bahram et al, 2013; Qian & Ricklefs, 2007). Those that did address distance gradients took an indirect approach by changing the grain of analysis (Keil et al, 2012, for multiple taxa across Europe; Kadowaki & Inouye, 2015, in an experimental fungivorous community; Batista et al, 2021, for Atlantic Forest bats). More directly, Cáceres et al (2014), using Mantel correlograms, reported that distance decay was most important at middle distances for birds and mammals in southwestern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, most examinations of environmental difference and geographic distance have done so at a single scale (e.g., Fluck et al, 2020; Stehn & Roland, 2018) or compared regions (e.g., Bahram et al, 2013; Qian & Ricklefs, 2007). Those that did address distance gradients took an indirect approach by changing the grain of analysis (Keil et al, 2012, for multiple taxa across Europe; Kadowaki & Inouye, 2015, in an experimental fungivorous community; Batista et al, 2021, for Atlantic Forest bats). More directly, Cáceres et al (2014), using Mantel correlograms, reported that distance decay was most important at middle distances for birds and mammals in southwestern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The use of alpha and beta diversities to determine productivity and ecosystem health has been useful and transversal, given that studies have been conducted both in terrestrial (Harrison et al 2006) and aquatic (Langenheder et al 2012, Bini et al 2014 ecosystems, studying different biological groups. This include benthic macroinvertebrates (Heino et al 2013), phytoplankton (Mousing et al 2016), macrophytes (Thomaz et al 2003), terrestrial insects (Kadowaki & Inouye 2015) and vertebrates (Martin & Ferrer 2015). Our study based on diatom assemblages was useful to infer the ecosystem's environmental health.…”
Section: Discussionmentioning
confidence: 99%
“…For example, flower abundance as habitat quality and habitat area have positive effects on the species richness of hoverflies and bees (Kleijn & Langevelde, 2006). Furthermore, the distribution of insect communities across the fragmented landscapes exhibits spatially correlated patterns due to habitat features such as vegetation cover that is also spatially correlated (Kadowaki & Inouye, 2015;Procheş et al, 2010). The spatial dependence in insect communities is the result of species responses to spatially correlated habitat features (Borcard et al, 1992(Borcard et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%